Mapping of the potential to substitute plastic in food packaging in finnish supermarkets - Lahtinen, Taina; Kataja, Kirsi; Viitanen, Jari; Kumar, Vinay; Lahtinen, Jussi; Harlin, Ali (Rochester Institute of Technology, 2024)
Single-use plastics (SUP), which are extensively utilized in food packaging, are one notable cause for the constantly growing littering issue. This novel study is one of the first attempts to systemically analyze food packaging data to reveal the potential for plastic packaging material reduction or substitution by utilizing a primary packaging material summary of single items sold in Finnish supermarkets. The outcome of the study indicates considerable dissimilarities among product groups concerning used packaging materials, weight, share of plastic, and sales volume. The analysis identified sweets and ready-to-eat meals as product groups for which there is a clear need, but also the most potential, to reduce the use of single-use plastics in food packaging. In these specific product groups, the sales share in euros is high (over 2%) and plastic is widely used (48–51%). The share of primary packaging material is also at a notable level (5–7%). Additionally, both product groups are significantly affected by the SUP directive and create a notable risk for littering. For ready-to-eat meals, the substitution potential of plastic is estimated to be close to 2,000 tonnes in Finland. Even so, sustainability is not solely accomplished by a replacement of the conventional packaging material with completely new solutions, and it is evident that there is no single and all-inclusive solution for future food packaging. Instead, the way to more environmentally friendly packaging combines several solutions of 4Rs - Reduce, Reuse, Replace, and Recycle.
Keywords: Food package; littering; single-use plastics; substitution; sustainable food packaging